Aspirin for Primary Stroke Prevention; Evidence for a Differential Effect in Men and Women - Gdovinova, Zuzana; Kremer, Christine; Lorenzano, Svetlana; Dawson, Jesse; Lal, Avtar; Caso, Valeria (Frontiers in Neurology, 2022)
Background: The use of aspirin for primary prevention of cardiovascular events in men and women remains controversial. Our study aimed to investigate the role of aspirin in primary stroke prevention in men and women and the effect of aspirin on risk of ischaemic stroke in patients with covert cerebral small vessel disease (ccSVD). Methods: We performed systematic searches of the PubMed, and Cochrane Library databases, covering the period from the inception of each database to May 2021; the incidence of stroke overall, both ischaemic (IS) and haemorrhagic (HS), was the main outcome. Results: From 531 abstracts, 11 randomised control trials were selected for primary prevention of cardiovascular events in men and women, only one study assessed the risk of aspirin in patients with ccSVD. In women, there was significant decrease in the risk of stroke (OR 0.85 [95% CI 0.73, 0.99], p=0.03) and IS (OR 0.76 [0.63, 0.93], p=0.008) with aspirin compared to placebo while no increase in the risk of HS was found (OR 1.78 [0.61, 5.19], p=0.29). In men, aspirin did not affect the risk of stroke (OR 1.13 [0.97, 1.31], p=0.12) and IS (OR 0.94 [0.67, 1.32], p=0.72) but increased the risk of HS with borderline statistical significance (OR 1.99 [0.99, 4.03], p=0.05) compared to placebo. Aspirin significantly increased major bleedings in both sexes (p<0.05). We found no evidence to support the use of aspirin in patients with ccSVD. Conclusion: Our meta-analysis suggests aspirin effect in primary prevention of stroke and IS in women with no increased risk of HS. However, it was associated with an overall increased risk of bleeding. Aspirin is not recommended in covert cerebral small vessel disease.